2019
DOI: 10.3892/mmr.2019.10569
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA/circRNA‑miRNA‑mRNA ceRNA network in lumbar intervertebral disc degeneration

Abstract: accumulating evidence has indicated that noncoding rnas are involved in intervertebral disc degeneration (idd); however, the competing endogenous rna (cerna)-mediated regulatory mechanisms in idd remain rarely reported. The present study aimed to comprehensively investigate the alterations in expression levels of circular rna (circrna), long noncoding rna (lncrna), microrna (mirna/mir) and mrna in the nucleus pulposus (nP) of patients with idd. in addition, crucial lncrna/circrna-mirna-mrna cerna interaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 58 publications
3
110
0
Order By: Relevance
“…Our results found miR-4450 was significantly up-regulated in IDD, which highlights its possible role in the pathogenesis of IDD, and the inhibition of miR-4450 may help protect NP. Two other studies further confirmed this trend [25,26]. Therefore, the overexpression of miR-4450 in NP of IDD patients highlights its possible role in the pathogenesis of IDD, and the inhibition of miR-4450 may help protect NP.…”
Section: Discussionmentioning
confidence: 65%
“…Our results found miR-4450 was significantly up-regulated in IDD, which highlights its possible role in the pathogenesis of IDD, and the inhibition of miR-4450 may help protect NP. Two other studies further confirmed this trend [25,26]. Therefore, the overexpression of miR-4450 in NP of IDD patients highlights its possible role in the pathogenesis of IDD, and the inhibition of miR-4450 may help protect NP.…”
Section: Discussionmentioning
confidence: 65%
“…Emerging evidences indicated that circRNAs sponged miRNAs to exert their biological functions [19][20][21], and hsa_circRNA_103809 facilitated cancer progressions by regulating miRNAs in a competing endogenous RNA (ceRNA)-dependent manner [14,[16][17][18]22]. By searching the online Pubmed database (https://pubmed.ncbi.nlm.nih.gov/), the miRNAs, including miR-101-3p [17], miR-532-3p [14], miR-4302 [18], miR-620 [22] and miR-377-3p [16], could be sponged by hsa_circRNA_103809.…”
Section: Discussionmentioning
confidence: 99%
“…According to our recent advances in circRNAs research, circRNAs exerted their biological functions and regulated genes expression through serving as RNA sponges to competitively bind to microRNAs (miRNAs) [19][20][21]. Taken hsa_circRNA_103809 as an example, previous publications indicated that hsa_circRNA_103809 sponged multiple RNAs, including miR-101-3p [17], miR-532-3p [14], miR-4302 [18], miR-620 [22] and miR-377-3p [16].…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding RNAs, which can regulate gene expression, are involved in many pathophysiological processes in intervertebral disc cells (6,7). MiRNA is a small, short-stranded fraction of lncRNA that binds to the 3'UTR of the target gene mRNA to inhibit mRNA translation or induce its degradation, thus regulating cell differentiation, proliferation, and survival (8).…”
Section: Introductionmentioning
confidence: 99%